Management of Orbital Masses: Outcomes of Endoscopic and Combined Approaches With No Orbital Reconstruction. (January 2020) - Rimmer, Ryan A.; Graf, Alexander E.; Fastenberg, Judd H.; Bilyk, Jurij; Nyquist, Gurston G.; Rosen, Marc R.; Rabinowitz, Michael P.; Rabinowitz, Mindy R.
Introduction: The endoscopic endonasal approach to management of orbital pathology has expanded. Due to the rarity of these conditions, most reports in the literature consist of small case reports. We report a series from a single institution with a focus on outcomes. Methods: A retrospective chart review was carried out between 2010 and 2018. Results: Twenty-four patients were identified (average age 58 years, 15 males, 9 females). Average follow-up was 14.9 months. Most common etiologies included cavernous hemangioma (7), metastases (6), idiopathic orbital inflammatory syndrome (6), orbital hematoma/clot (2), and schwannoma (1). Most common presenting symptoms were decreased visual acuity (8), proptosis (8), diplopia (7), and incidental findings (2). All patients underwent endoscopic medial wall orbital decompressions. Sixteen involved a combined open approach by an ophthalmologist. Pathology was either biopsied (15), resected (6), or could not be identified (3). No intraoperative complications were noted. No patients underwent orbital reconstruction of the medial wall. Six patients developed postoperative sinusitis successfully managed with antibiotics. One patient developed epistaxis managed conservatively. In 5 patients, Sino-Nasal Outcome Test-22 scores increased immediately postop and then decreased, whereas scores only decreased in 6 patients. Six patients noted reduced proptosis. There were no new cases of diplopia or worsening visual acuity. Conclusions: A combined endoscopic endonasal and external approach can be useful for managing orbital lesions. Patients tolerated the procedure well with improvement in ocular symptoms and minimal sinonasal complications. Reconstruction of the medial wall may not be warranted to prevent postoperative diplopia.